2019
DOI: 10.3390/app9102025
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time GPU-Based Digital Image Correlation Sensor for Marker-Free Strain-Controlled Fatigue Testing

Abstract: Digital image correlation (DIC) is a highly accurate image-based deformation measurement method achieving a repeatability in the range of   σ =   10−5 relative to the field-of-view. The method is well accepted in material testing for non-contact strain measurement. However, the correlation makes it computationally slow on conventional, CPU-based computers. Recently, there have been DIC implementations based on graphics processing units (GPU) for strain-field evaluations with numerous templates per image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In general, the LSP technique provides a solution for fast in-line inspections in the industrial field. It has already been used several times to characterize material properties, such as hardness and porosity, but also to detect defects in metallic components (Bendjus et al, 2012;Cikalova et al, 2012a, b). In contrast to metals, ceramic materials have very different thermal and mechanical properties.…”
Section: Laser Speckle Photometrymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the LSP technique provides a solution for fast in-line inspections in the industrial field. It has already been used several times to characterize material properties, such as hardness and porosity, but also to detect defects in metallic components (Bendjus et al, 2012;Cikalova et al, 2012a, b). In contrast to metals, ceramic materials have very different thermal and mechanical properties.…”
Section: Laser Speckle Photometrymentioning
confidence: 99%
“…Traditional techniques such as the X-ray diffraction method (Gao et al, 2017;Xi et al, 2017), Raman spectroscopy (Jan-notti et al, 2017), and the hole-drilling method (Mainjot et al, 2011) are time-consuming, expensive, and sometimes destructive. In addition, speckle photography is a full-field optical method and, by combining it with the digital image correlation technique, can be used to measure in-plane deformations and strains in opaque materials (Blug et al, 2019;Schenuit et al, 2008;Tausendfreund et al, 2018). It records the speckle patterns before and after the deformation of the inspected workpiece.…”
Section: Introductionmentioning
confidence: 99%
“…To address the speedup challenge faced by multicore realizations, testing of DIC algorithms by deploying GPUs is published in previous studies . The key idea of these works is to improve computational speed of DIC by using the potential offered by the recent developments in parallel computing domain.…”
Section: Introductionmentioning
confidence: 99%
“…Blug et al reported a marker‐free GPU‐based DIC measurement system for both strain‐controlled fatigue testing and strain evaluation in real time . In addition, the authors also proposed a GPU‐based path‐independent video extensometer for real‐time closed‐loop applications . The emphasis in these two works however is on measurement of strain.…”
Section: Introductionmentioning
confidence: 99%
“…Digital image processing has been applied widely, in such cases as in control level for industries [12], which is based on the treatment of a special light shape generated by a laser, also measuring displacements in infrastructures by a matrix of points [13]. Some researchers around the application in engineering are evaluating the curvature of a pipeline using a parabolic function to determine its deformation [14], analyzing the location of cracks in reinforced concrete by monitoring the surface deformation with two cameras [15], strain measurements during film stretching process following the digital changes of the marker [16], and measuring the strain in time for standardized fatigue tests [17], among others.…”
Section: Introductionmentioning
confidence: 99%